Recessive mutations in >VPS13D cause childhood onset movement disorders. Issue 6 (10th April 2018) - Gauthier, Julie; Meijer, Inge A.; Lessel, Davor; Mencacci, Niccolò E.; Krainc, Dimitri; Hempel, Maja; Tsiakas, Konstantinos; Prokisch, Holger; Rossignol, Elsa; Helm, Margaret H.; Rodan, Lance H.; Karamchandani, Jason; et al.
Abstract : VPS13 protein family members VPS13A through VPS13C have been associated with various recessive movement disorders. We describe the first disease association of rare recessive VPS13D variants including frameshift, missense, and partial duplication mutations with a novel complex, hyperkinetic neurological disorder. The clinical features include developmental delay, a childhood onset movement disorder (chorea, dystonia, or tremor), and progressive spastic ataxia or paraparesis. Characteristic brain magnetic resonance imaging shows basal ganglia or diffuse white matter T2 hyperintensities as seen in Leigh syndrome and choreoacanthocytosis. Muscle biopsy in 1 case showed mitochondrial aggregates and lipidosis, suggesting mitochondrial dysfunction. These findings underline the importance of the VPS13 complex in neurological diseases and a possible role in mitochondrial function. Ann Neurol 2018;83:1089–1095